Present-Day Tectonic Deformation Partitioning Across South Tianshan From Satellite Geodetic Imaging - Qiu, Jiangtao; Ji, Lingyun; Zhu, Liangyu; Wang, Qingliang (Frontiers in Earth Science, 2022)
The Tianshan orogenic belt has intense crustal deformation and shortening in the near north-south direction. We processed ascending and descending Sentinel-1A/B synthetic aperture radar (SAR) data to obtain the first line-of-sight deformation field over South Tianshan (75–78 E), and combined with GPS velocity data to construct the current three dimensions surface velocity fields with high quality and high spatial resolution. The results show that: (1) deformation is not evenly distributed in the study area. The convergence across the Tianshan ranges is approximately 15–24 mm/yr; the deformation gradient in the junction area between South Tianshan and Pamir is the largest, and adjusts ~68% of the total convergence deformation. South Tianshan is relatively stable without sharp gradients, and ~58% of the deformation is distributed in the intermontane faults and basin systems in the north of South Tianshan. (2) Thrust slip of faults, uplift of folds, and slippage of décollement jointly play important roles in accommodating regional strain. The Maidan fault, which is the boundary between South Tianshan and Tarim Basin, has strike-slip and thrust characteristics, and is the root fault of the slip partitioning system. Our results can provide effective kinematic boundary constraints for the study of Asian crustal movement models.